KEEFEKTIFAN MODEL SCRAMBLE DALAM PEMBELAJARAN MEMBACA PEMAHAMAN UNTUK MENEMUKAN GAGASAN UTAMA - Langke, Alimuddin (Makassar Journal of Social Sciences, 2015)
Abstract: This study generally aims to determine the ability and the difference value of class VII SMP Al-Bayan Makassar in the experimental group in reading comprehension to find the main idea by applying the model (Scramble), and the control group in reading comprehension class to find the main idea without applying the model (Scramble). This type of research is experimental study consisted of quantitative descriptive analysis and presented in tabular form through the calculation of average and percentage. In this study there were two groups include the experimental group and the control group. Subjects in this study were students of class VII A, amounting to 26 people and class VII B SMP amounted to 32 people in Al-Bayan Makassar This research was conducted on the academic year 2013-2014. Class experiments conducted on Setember 15-24, 2014. The results showed that reading comprehension achievement test to find ideas on classroom control, ie: 79.03% and the experimental class increased to 82.85%. In addition, the allocation of time in the schedule provided is inadequate, whereas this method requires a lot of time in implementing them. But these constraints can be handled properly so that the learning process is still running as expected